Compressive Strength Analysis of Solid Cylindrical Concrete K250 and K300: Effect of Curing Method on 28-Day Performance - Riham Arfiyah; Zaenal Abidin; Muhammad Reza Falakhuddin (Penerbit Goodwood, 2025)
Purpose: This study aims to determine and analyze the compressive strength of K250 and K300 concrete cylindrical specimens tested at 28 days, and to explain the mechanism by which differential curing methods applied to the two grades produced counterintuitive strength outcomes in the context of a nuclear technology education facility.Methodology: Compressive testing was conducted on five K250 and five K300 concrete cylindrical specimens (diameter 150 mm x height 300 mm) at 28 days using a Cernusco Compression Testing Machine (Model 20063). K250 specimens underwent 28-day continuous water immersion, whereas K300 specimens received only ambient air curing from the date of casting. Compressive strength values were recorded, group means were computed, and results were compared against design strength targets per PBI 1971.Results: K250 water-cured specimens produced a mean compressive strength of 346.28 kg/cm², exceeding the 250 kg/cm² design target by 38.5%. Air-cured K300 specimens attained only 287.87 kg/cm², falling below their 300 kg/cm² design target, resulting in K250 outperforming K300 by 58.41 kg/cm².Conclusions: Curing method overrides nominal mix design grade as the controlling determinant of 28-day compressive strength. Limitations: The small sample of five specimens per grade and the absence of controlled mix design parameters limit generalizability.Contributions: This study provides an empirical case study of the compressive strength consequences of differential curing conditions on K250 and K300 concrete, offering practical evidence for construction quality control protocols in nuclear technology and general engineering facility contexts.